Proceedings of the International Conference on Advanced Intelligent Systems and Informatics 2016 - Hassanien, Aboul Ella.; Shaalan, Khaled; Gaber, Tarek; Azar, Ahmad Taher; Tolba, M. F.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book gathers the proceedings of the 2nd International Conference on Advanced Intelligent Systems and Informatics (AISI2016), which took place in Cairo, Egypt during October 24-26, 2016. This international interdisciplinary conference, which highlighted essential research and developments in the field of informatics and intelligent systems, was organized by the Scientific Research Group in Egypt (SRGE) and sponsored by the IEEE Computational Intelligence Society (Egypt chapter) and the IEEE Robotics and Automation Society (Egypt Chapter). The book's content is divided into four main sections: Intelligent Language Processing, Intelligent Systems, Intelligent Robotics Systems, and Informatics.
Further Investigations for Documents Information Retrieval Based on Discrete Wavelet Transform -- Knowledge Representation in Intelligent Tutoring System -- A new method for interoperability between lexical resources using MDA approach -- Optimizing Fuzzy Inference Systems for Improving Speech Emotion Recognition -- Arabic fine-grained opinion categorization using discriminative machine learning technique -- A Spell Correction Model for OCR Errors for Arabic Text -- Natural Language Processing for Arabic Metaphors: A Conceptual Approach -- Using Text Mining To Analyze Real Estate Classiﬁeds.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence